Chemical structure predicts the effect of plant‐derived low‐molecular weight compounds on soil microbiome structure and pathogen suppression. (31st July 2020) - Gu, Yian; Wang, Xiaofang; Yang, Tianjie; Friman, Ville‐Petri; Geisen, Stefan; Wei, Zhong; Xu, Yangchun; Jousset, Alexandre; Shen, Qirong
Abstract: Plant‐derived low‐molecular weight compounds play a crucial role in shaping soil microbiome functionality. While various compounds have been demonstrated to affect soil microbes, most data are case‐specific and do not provide generalizable predictions on their effects. Here we show that the chemical structural affiliation of low‐molecular weight compounds typically secreted by plant roots—sugars, amino acids, organic acids and phenolic acids—can predictably affect microbiome diversity, composition and functioning in terms of plant disease suppression. We amended soil with single or mixtures of representative compounds, mimicking carbon deposition by plants. We then assessed how different classes of compounds, or their combinations, affected microbiome composition and the protection of tomato plants from the soil‐borne Ralstonia solanacearum bacterial pathogen. We found that chemical class predicted well the changes in microbiome composition and diversity. Organic and amino acids generally decreased the microbiome diversity compared to sugars and phenolic acids. These changes were also linked to disease incidence, with amino acids and nitrogen‐containing compound mixtures inducing more severe disease symptoms connected with a reduction in bacterial community diversity. Together, our results demonstrate that low‐molecular weight compounds can predictably steer rhizosphere microbiome functioning providing guidelines to engineer microbiomes based on root exudation patterns by specific plant cultivars or crop regimes. A free plain language summary can be found within the Supporting Information of this article. Abstract : A free plain language summary can be found within the Supporting Information of this article.